Strategi Media Relation Humas Pemerintah Kota Bekasi dalam Meningkatkan Citra Lembaga - Amaruddin Taufiqurrohman; Mohammad Luthfi (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2024)
Government public relations has a very crucial role in maintaining a positive image of the institution, one of which is through media relations strategies. This research aims to determine the Bekasi City Government Public Relations media relations strategy in improving the institution's image referring to media relations strategy theory with three indicators; managing relationships, developing strategies, and developing networks. The research approach used is qualitative with a case study method. Data collection through interviews, observation and documentation. The research results show that Bekasi City Government Public Relations implements a media relations strategy through intensive communication with the media both verbally and non-verbally, carrying out media relations activities such as coffee mornings, press conferences and press releases. In developing the strategy, several efforts have been made, such as creating new concepts, providing the latest information, becoming a valuable resource, and following up on negative news. Meanwhile, at the network development stage, collaboration has been carried out with students, the police, Gojek application providers and the media. This research provides implications for scientific development, especially public relations and has a practical impact in implementing public relations activities through media relations strategies.